Effectiveness of aquatic plants as phytoremediation in palm oil processing factory wastewater - Mustaqim Mustaqim; Wenny Novita Sari; Irfannur Irfannur; Yusrizal Akmal; Muliari Muliari (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
The research aims to see the effect of using kale (Ipomoea Aquatica), water hyacinth (Eichhornia crassipes) and apu-apu (Pistia statiotes) in the phytoremediation process on water quality in palm oil mill waste. The design used in this research is an experimental design using a non-factorial Completely Randomized Design (CRD). The treatments in the study used 4 treatments and three replications, namely P1: 20 liters of palm oil waste + 600 grams of water spinach, P2: 20 liters of palm oil waste + 600 grams of water hyacinth, P3: 20 liters of palm oil waste + 600 grams of apu-apu, P4: 20 liters of palm oil waste. The observation parameters in this study include pH, DO, Temperature, Nitrate and Phosphate. The results showed that the best aquatic plants in phytoremediation of palm oil wastewater were in treatment B (water hyacinth) and the lowest in treatment D (control). From the results obtained, it can be concluded that water hyacinth is suitable for use as a plant in phytoremediation and is able to improve the quality of palm oil wastewater.